2008
DOI: 10.1136/emj.2007.054338
|View full text |Cite
|
Sign up to set email alerts
|

Norwegian regular general practitioners' experiences with out-of-hours emergency situations and procedures

Abstract: Approximately two-thirds of RGPs in Norway took part in the out-of-hours service. A wide variety of emergency cases was experienced by the RGPs. Despite this, experiences with most emergency procedures during a 12-month period are low. Regular training is therefore necessary to maintain good skill levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 9 publications
2
13
0
4
Order By: Relevance
“…A paper from 2009 investigating emergency medicine in a rural community suggested mandatory training on a regular basis for GPs taking part in out-of-hours work, supporting the view of our informants [7]. The need for interdisciplinary training as described by the EMTs has also been found in previous studies [6],[15]. …”
Section: Discussionsupporting
confidence: 80%
“…A paper from 2009 investigating emergency medicine in a rural community suggested mandatory training on a regular basis for GPs taking part in out-of-hours work, supporting the view of our informants [7]. The need for interdisciplinary training as described by the EMTs has also been found in previous studies [6],[15]. …”
Section: Discussionsupporting
confidence: 80%
“…A study found geographical differences in the involvement of Norwegian doctors on-call in pre-hospital emergencies, but the study was limited to situations where the air ambulances were alerted as well [6]. Two studies have investigated rGPs'experiences with emergency situations, though not red responses in particular, through the EMCC system [7,8]. On a national basis the EMCCs in Norway alerted doctors on-call in about 50% of the red response cases [9].…”
Section: Introductionmentioning
confidence: 99%
“…The general practitioners and urgent care centres have been assigned a key role as gatekeepers for the specialist health services including the EDs,15 and it is therefore not a surprise that a large portion of our patient population arrive from the urgent care centre. Surprisingly, around 15% of the assumed low acuity patients seen at the urgent care are transferred to the ED.…”
Section: Discussionmentioning
confidence: 99%